PENGARUH EKSTRAK MARKISA (Passiflora edulis varietas flavicarpa) TERHADAP FEEDING STRATEGY LALAT BUAH Bactrocera dorsalis He nd. - Oktavia, Delni; Sumarmin, Ramadhan; Ze swita, Armein Lusi (Pendidikan Biologi, 2013)
Marquisa is one of favourite fruit in Indonesia. However this plant is oftenattacked by diseases, one of them is Bactrocera dorsalis. There is no information yetabout what interest Bactrocera dorsalis to marquisa does. Based on the problem, theaim of the research is effect of marquisa extrac t (Passiflora edulis varietas flavicarpa)toward Feeding Strategy of fruit fly Bactrocera dorsalis Hend. T his research wasexperimental research used cilinder Y tube method, with match treatment and includes10 repetitions. The research was conducted from October 2012 to February 2013. Theresult, show that marquisa extract have effect toward Feeding Strategy from fruit flyBactrocera dorsalis. On the searching activity, the fastest time of fruit fly reachedmarquisa was at the treatment V (75,13 seconds) although longest time was at treatmentI (256,33 seconds). On the grounding ac tivity, the fastest time of fruit fly reachedmarquisa was at the treatment V (45,23 seconds) although the longest time of treatmentI (58,7 seconds). Based on Chi-square analysis the treatment had the higher differencebetween petrogenol and marquisa extract, excepting treatment 3 ml of marquisa extractand 3 drops of petrogenol did not have real difference between petrogenol and marquisaextrac t. It cand conclude that marquisa extract had effect toward Feeding Strategy offruit fly Bactrocera dorsa lis.